Conceptual Foundations of Societal Modernization - Nargiza, Seydabullaeva (Indonesian Journal Publisher, 2024)
The article emphasizes that today, when the processes of integration and globalization in the social, economic, and spiritual spheres are intensifying in the world, special attention should be paid to analyzing the problems accumulated in the directions of societal modernization, developing conceptual models, and analyzing them. The political and philosophical analysis of democratic development processes and the improvement of its management system. In the transition period, the exchange of political systems described in scientific sources considers three development models, the goal of modernization. In the second half of the 20th century and the beginning of the 21st century, new views were expressed on the content and significance of the concept of modernization. Political modernization is a complex process. In it, social-economic, political-legal and socio-cultural spheres are interconnected, give content to each other, and if there is a rift between them, then modernization will not increase if it is not fully realized. It has been deeply analyzed that if the incomes of social strata in society are sharply differentiated, effective economic growth will not be achieved, if a perfect personality with a cultural level is not formed, market structures will not be formed, if civil society institutions are not developed, democratic values will not be developed.